(untitled) (Web of Teachers: Inderscience Research, 2025)
The article presents the views of researchers on the concept of tragedy. Albert Camus’s works raise complex issues related to the absurd. Camus deeply analyzes tragedy in a number of his works related to the philosophy of the absurd and existentialism.